SELECTION OF AN APPROPRIATE VENOUS ACCESS IN A NEWBORN - Eva Ojsteršek; Jana Lozar Krivec; Janja Gržinić; Renata Vettorazzi (Slovenska pediatrija)

(untitled)
Venous access is essential for the safe and effective treat-ment of sick, hospitalized newborns. Possible venous accesses that can be established in a newborn are peripheral intravenous cannula, central venous catheter, peripherally inserted central catheter (PICC) and umbilical venous catheter. The choice appropriate approach depends on the newborn’s health status, expected duration of intravenous therapy, and solution properties. Umbilical venous catheter is the first choice for critically ill newborns, enabling intensive treatment but should be removed within five to seven days due to a high risk of complications. If the newborn remains unstable, central venous catheter is inserted for high-flow administration and hemodynamic monitoring. If the newborn is stable after umbilical catheter removal, the next venous access is determined by the expected infusion duration. For therapy exceeding seven days or requiring solutions incompatible with a peripheral route, PICC is preferred; otherwise, a peripheral intravenous cannula is used. Venous access methods vary in puncture site, catheter tip location, size, and number of lumens, leading to different functions and risks. A careful selection of the appropriate venous access is essential to minimize complications and ensure effective treatment.